CFD modeling and experimental verifications of a four-stage Stirling-type pulse tube cryocooler. (April 2019) - Zha, Rui; Zhang, Tao; Li, Jiaqi; Tan, Jun; Zhao, Yongjiang; Zhao, Bangjian; Dang, Haizheng
Abstract: This paper conducts CFD modeling and experimental verifications of a four-stage Stirling-type pulse tube cryocooler (SPTC) aimed to reach liquid helium temperature for low Tc superconducting devices and deep space exploration. A two-dimensional (2-D) axis-symmetric CFD model with the thermal non-equilibrium mode is developed to simulate the internal operating mechanism. A cryogenic phase-shifting approach is employed to improve the phase conditions. Several cases are set to study the phase relationship between mass flow rate and dynamic pressure at the inlet and outlet of the regenerator. The effects of the operating frequency on flow and heat transfer processes in the pulse tube are also investigated. Based on the above numerical studies, a four-stage thermally-coupled SPTC is then developed and tested. It reaches a no-load temperature of 4.5 K and achieves cooling capacities of 10.5 W/80 K, 8.6 W/60 K, 1.5 W/30 K and 10 mW/5 K experimentally.